APPROACHES AND METHODS TO TEACHING GRAMMAR IN TEXTBOOKS FOR STUDENTS AT ABA BALIKPAPAN - Muhammad Rochman (UIBU, 2023)
This study aims to describe, compare, and contrast approaches and methods to teaching grammar in textbooks used in First Semester of English Department Students at ABA Balikpapan. It chooses, as samples for analysis, textbooks of one particular class to focus on the approaches to teaching grammar in these textbooks. These textbooks are taught for first intermediate class and belong to two different series titled First Semester of English Department Students at ABA Balikpapan opportunities and English for First Semester of English Department Students at ABA Balikpapan. Each of these textbooks follows essentially different approaches to teaching grammar. This study aims to highlight the similarities and differences between the books and reveals the weaknesses and strengths of the approaches in these books. The purpose of the study is changing these textbooks and to reveal the similarities and differences between the old and new textbooks. The data collection method of this research is the collation texts for analysis. The information is breaking down subjectively and quantitatively. The study considerably contributes to the field of language teaching in First Semester of English Department Students at ABA Balikpapan especially grammar teaching through drawing attention of language lecturers, textbook writers, as well as learners to a certain degree, to the weaknesses and strengths of the PPP method (Presentation Practice Production) in the First Semester of English Department Students at ABA Balikpapan opportunities textbook and task-based approach in the English for First Semester of English Department Students at ABA Balikpapan textbook.